Diaper rash treated with chlorhexidine. Clinical results and changes in the bacterial flora. - Bonifazi, E.; Miragliotta, G.; Caprio, F.; Favale, M.; Mosca, A.; D'Alagni, M. (European Journal of Pediatric Dermatology, 2018)
Diaper rash is a common irritant contact dermatitis. It is caused by numerous factors, inclusive of bacterial agents. Chlorhexidine is a well known antiseptic, which is frequently used in the treatment and prevention of the infectious diseases of the skin and mucous membranes. In this study 4% chlorhexidine aqueous solution was used as only treatment in 21 children with diaper rash. The Authors studied the changes in the bacterial flora after the use of the drug and assessed its tolerance and effectiveness.